Formation of Project Identity in a Multi-Project Environment - Emmanuel Nyameke; Harri Haapasalo; Kirsi Aaltonen (International School for Social and Business Studies, 2020)
Managing multiple projects concurrently is an effective way to handle modern business projects. However, management of project multiplicity is still a challenge in the construction industry, and the project identity is considered fundamental for success of a project. This study seeks to deepen the understanding of multi-projects and to outline key features that constitute the process of managing projects simultaneously in multi-project environments within project-based organisations. A case study with two renowned construction companies in Finland was undertaken to identify five processes that constitute project identity in a multi-project environment. These processes include: (1) articulating a multi-project environment vision and goals; (2) managing the allocated recourses and schedule for a multi-project environment; (3) establishing adequate communication systems for a multi-project environment; (4) establishing stakeholders' management and paying attention to documentation details; and (5) providing adequate training and establishing an innovation-adaptive box. These results will assist project-based organisations in developing and managing projects concurrently in a multi-project environment.